The Programme for National Education (1914-1924), or: how a Forced Cultural Transfer Fails - Giudici, Anja; Manz, Karin (Swiss Journal of Educational Research, 2018)
This article analyses the so-called programme of national education as a (failed) case of a domestic, forced cultural transfer. This programme, developed by the liberal elite during World War One, aimed at preventing Switzerland’s disintegration through a stronger focus on Swiss history, political education, and the teaching of Swiss languages in curricula. However, the programme failed because of the opposition exerted by the Catholic-Conservative Party and the Social-Democratic Party as well as by the cantons’ representatives. We frame this case as a forced cultural transfer and outline how this concept can add new perspectives to the research on cultural transfers, which up to now focused on voluntary, transnational processes of adaptation and appropriation, steered by the beneficiaries of such exchanges. Our take permits to consider institutional factors as well as deliberate and failed exchange processes.